(untitled) (Multidisciplinary Journal of Science and Technology, 2024)
Agricultural biostimulants are considered biological and include biologically beneficial fertilizers and similar products used in the production of plant products to increase the growth, health and productivity of plants. This article provides extensive information on what biostimulants are and the effects of biostimulants on the growth and development of agricultural products.